Nanotechnology formulations for antibacterial free fatty acids and monoglycerides - Li, Danlin (2018)
Free fatty acids and monoglycerides have long been known to possess broad-spectrum antibacterial activity that is based on lytic behavior against bacterial cell membranes. Considering the growing challenges of drug-resistant bacteria and the need for new classes of antibiotics, the wide prevalence, affordable cost, and broad spectrum of fatty acids and monoglycerides make them attractive agents to develop for healthcare and biotechnology applications. The aim of this review is to provide a brief introduction to the history of antimicrobial lipids and their current status and challenges, and to present a detailed discussion of ongoing research efforts to develop nanotechnology formulations of fatty acids and monoglycerides that enable superior in vitro and in vivo performance. Examples of nano-emulsions, liposomes, solid lipid nanoparticles, and controlled release hydrogels are presented in order to highlight the potential that lies ahead for fatty acids and monoglycerides as next-generation antibacterial solutions. Possible application routes and future directions in research and development are also discussed.